IMPLEMENTASI ELECTRONIC PUBLIC RELATIONS (E-PR) SEBAGAI RUANG INFORMASI PUBLIK DALAM TRANSFORMASI TEBET ECO PARK - wukir, Iswahyu; Alamsyah, Alamsyah; Suandi, Fikri; Hitopa Sukma, Agus (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2024)
This study aims to analyze the implementation of Electronic Public Relations (E-PR) as a public information space in the transformation of Tebet Eco Park. The research method used is descriptive qualitative with the type of case study research. Data were obtained through in-depth interviews with relevant informants, participant observation and document analysis. The results of the study show that the implementation of E-PR in the transformation of Tebet Eco Park has succeeded in increasing access to public information and community participation in decision making regarding the management of urban parks. The implementation of E-PR in the transformation of Tebet Eco Park has succeeded in increasing access to public information and community participation in making decisions regarding park management. E-PR is used optimally as a means of conveying public information through websites, social media and mobile applications.